A novel CWPO/H2O2/VUV synergistic treatment for the degradation of unsymmetrical dimethylhydrazine in wastewater. Issue 3 (28th January 2021) - Meng, Xu; Zeng, Pingchuan; Wang, Junru; Shao, Yamin; Wu, Min; Ni, Henmei; Zheng, Yingping; Sun, Yueming
ABSTRACT: In this paper, the catalytic wet peroxide oxidation (CWPO) combined with vacuum ultraviolet (VUV) irradiation was developed to mineralize the wastewater with high concentration of unsymmetrical dimethylhydrazine (UDMH), especially to decompose the main byproduct of UDMH decomposition, N-nitrosodimethylamine (NDMA). CuO–NiO–MgO/γ-Al2 O3 was used as the catalyst and H2 O2 as the resources of ⋅ O H . Fourier Transform Infrared spectroscopy (FT–IR), X-ray Powder Diffraction (XRD), Scanning Electron Microscopy (SEM) and Energy-Dispersive X-ray spectroscopy (EDX) were employed to evaluate the structure of the catalyst. The treatment performances such as the UDMH degradation efficiency, chemical oxygen demand (COD) removal efficiency, and the concentration of N-nitrosodimethylamine (NDMA) were investigated in the treating process. The optimal conditions were obtained based on the results of single-factor experiments including parameters such as the initial UDMH concentration, catalyst dosage, initial pH, H2 O2 dosage and temperature. The comprehensive results indicated that CWPO/H2 O2 /VUV process presented remarkable treatment performance to the reaction conditions with about 100% UDMH conversion efficiency, 95.02% COD removal efficiency and approximately 100% UDMH removal within 30 min. GRAPHICAL ABSTRACT: UF0001